Long-term controlled antihypertensive therapy in Chernobyl liquidators, its effectiveness and benefits - I. I. Razdobreeva; S. K. Kukushkin; E. M. Manoshkina; E. Yu. Zvolinskaya; N. V. Brezak; N. A. Zemtsova; G. A. Muromtseva; S. A. Shalnova (Кардиоваскулярная терапия и профилактика, 2005)
Aim. To compare effectiveness of controlled antihypertenive therapy (AHT) and standard outpatient care among Chernobyl male liquidators (ML) with mild to moderate arterial hypertension (AH). Material and methods. This 12-month, open, comparative randomized study included 81 ML aged 37-70, with mild to moderate AH. The main group consisted of 42 patients, the control group – of 39; mean age 52.2±1.3 and 51.5±1.1 years, mean AH duration 10±1 and 9.6±1 years, respectively. In main group, patients received an ACE inhibitor spirapril, combined with hypothiazide (12.5-25 mg/d), and atenolol (12.5-100 mg/d), if necessary. In control group, AHT and its correction were performed by outpatient physicians. Medical history collection, physical examination, anthropometry, blood pressure (BP) measurement (three times), and electrocardiograpy were performed. Results. During one-year controlled AHT, comparing to standard outpatient care, more effective decrease in systolic and diastolic BP was achieved. Antihypertensive effect was registered in 78.6% and 38.0% of the main and control group patients, respectively. At the end of the study, most participants from the main group ((78.6%) received combined therapy (2 or more drugs); in control group, this number was only 17.2%. Conclusion. The results of the study demonstrated high effectiveness and benefits of long-term controlled AHT, comparing to standard outpatient care.